Consensus Document on the Use of Avastin (Bevacizumab) in Retinal pathologies - -, - - (Pakistan Journal of Ophthalmology, 2011)
BACK GROUND This document was created, debated, amended and approved by the members of the vitreoretinal association of Pakistan. This exercise was carried out on behalf of the Ophthalmic Society of Pakistan. The central council of the OSP had expressed with concern that while the use of Avastin was increasing exponentially, most Ophthalmic practioners had limited knowledge and experience in the use of this drug. There was as yet no information available in textbooks. It was therefore incumbent on the people who had acquired the most knowledge of this drug to share their knowledge and the fruit of their experience for the benefit of patients. Vitreo Retinal Association of Pakistan (VRAP) therefore took up this task.